Rinascimento virtuale-Digitale Palimpsestforschung: Nuevas tecnologías y recuperación de palimpsestos (con especial atención a los conservados en bibliotecas españolas) - Escobar, Ángel (Euphrosyne, 2004)
Abstract This paper tries to explain some aspects of the history, nature and use of palimpsests in the ancient Graeco-Roman world, and it gives some general informations about the evolution of this kind of documents (production, geographical distribution, textual relevance) during the Middle Ages on the basis of some examples. After a brief consideration about the modem technical possibilities for the digital study of palimpsests, we give a report about the analysis of palimpsests in Spanish libraries, paying special attention to the Matritensis 4554.